Towards a grounded theory of why and how coopetition emerges among SMEs: revisiting intentionality and unintentionality - Kauami, Ngunoue Cynthia (Graduate School of Business (GSB), 2025)
Over the past three decades, there has been growing research interest in coopetition. Coopetition is an intricate network of interdependencies among firms, where intentional and unintentional cooperation and competition occur concurrently. This occurs towards the achievement of diverse yet mutually advantageous recurring economic and/or altruistic objectives, endorsing a paradoxical relationship. While research has advanced, little remains known about the fundamentals of the emergence of coopetition. This study uses strategy-as practice and processual lenses to consider why and how coopetition emerges, delving into the lived experiences of tourism business owners/managers to allow for a micro-foundational view of emergence. Using a qualitative constructivist grounded theory approach, data were collected among small and medium enterprises (SMEs) and analysed over a period of one year at the tourism destinations of Swakopmund and Walvis Bay in Namibia. Theoretical saturation was attained at 89 episodes of emergence, since emergence was adopted as the level analysis. The study found three typologies of coopetition emergence: economic, altruistic, and habitual coopetition. Economic coopetition emergence, underlined by resource deficiency, alliance and diversification logics is confirmed in extant literature and has been considered as the dominant reason for competitors engaging collaboratively. This typology emerges both intentionally and unintentionally. Altruistic coopetition emergence, that is driven by solidarity and identity logics confirms and extends recent studies which maintain that there are non-economic reasons for coopetition emergence. This typology was found to emerge unintentionally. Economic and altruistic emergence have recurring patterns over time, which give rise to habitual coopetition emergence. This coopetition type is indicative of practices that become embedded and implicitly institutionalised as modus operandi with consistent reciprocal recurrence driven by economic and altruistic logics, albeit mutually exclusively. Emergence is a process that unfolds in four overarching phases: the selection, negotiation, delivery, and review phases, which are foundational expressions of how the three typologies manifest, confirming its episodic nature which can be deemed to go through “life cycles”. The study contributes to the coopetition literature in general, and specifically to the formation stage by strengthening the non-economic rationale of emergence through presenting care ethics, considered in psychology and social neurosciences. Furthermore, habitual emergence advances path dependence, trust and reciprocity literature and the significant role of time in coopetition intent. From a practical perspective, the study contributes to increased managerial insights into the best ways to structure coopetition, considering the different typologies and emergence processes for enhanced financial and non-financial benefits. In addition, it furthers the idea of sustained coopetitive relationships among firms in general, and among small and medium enterprises (SMEs) specifically.